Judicial construction and technical expertise as a means of protecting the interests of participants of building process - Butyrin Andrey; Stativa Ekaterina (MATEC Web of Conferences, 2018)
The paper defines the significance of judicial construction and technical expertise as a means of protecting the rights and interests of participants of building process when considering and resolving economic and industrial disputes, significant number of which is based on the imperfect legal regulation of public relations of this activity. Noting the insufficient knowledge of the judicial community about the informational potential of this kind of judicial expertise, the authors presented a wide range of types of studies conducted by the building expert in practice. The presented list includes the following types of studies of the object of judicial construction and technical expertise: establishment of its existence; location; technical condition; its properties; qualitative and quantitative characteristics; cost; an object's belonging to a particular class, sort, kind, type, group; establishment of the conformity of its characteristics to a certain standard, rule or regulation. Consideration is also made of studies that have been conducted in judicial and investigation expert practice aimed at establishing the presence and types of causal connection between events that have been the subject of criminal investigation and (or) judicial proceeding, as well as establishing the object’s existence by its representation, belonging of a part of the object to the whole, definition of a unified source of origin (manufacturer) of several objects of judicial construction and technical expertise.